An Inventory of Poisonous Plants of Sagar District, Madhya Pradesh (India) - Choubey, V. B.; Khare, P. K. (Indian Forester, 2011)
Important wild and cultivated poisonous plants of Sagar district, Madhya Pradesh (India) were recorded during survey in deciduous forests and surrounding area of the district. Total number of 52 species belonging to 25 families were collected. Out of these, 32 Herbs, 14 shrubs and 06 trees were classified. These species are known to possess different toxic and poisonous properties used for various purposes like brain, cardiac, blood poisoning, etc. Toxic plant part, toxic principles, toxicity, local name, family and habit ofthese plants are described and discussed.